Analisis Yuridis terhadap Tindak Pidana Peredaran Sediaan Farmasi yang Tidak Memenuhi Standar Keamanan, Khasiat, Kemanfaatan dan Mutu (Studi Putusan Pengadilan Negeri Serang Nomor 551/Pid.Suss/2025/PN Srg) - Ria Natalia; Ratih Kemala (Decisio: Jurnal Ilmiah Hukum, 2026)
The circulation of pharmaceutical preparations that do not meet standards of safety, efficacy, usefulness, and quality constitutes a serious problem in the health law system because it may endanger public safety. This study aims to analyze the legal regulation of pharmaceutical preparations circulation in the Indonesian health law system and the application of such legal provisions in the a quo case, namely Serang District Court Decision Number 551/Pid.Sus/2025/PN Srg. This research uses a normative legal research method with statutory and case approaches. The results show that the regulation of pharmaceutical preparations has been clearly stipulated in Law Number 17 of 2023 concerning Health, particularly regarding the obligation to fulfill standards of safety, efficacy, usefulness, and quality, as well as the prohibition on distributing medicines without legal authority. In the a quo case, the defendant was legally and convincingly proven to have possessed and distributed hard drugs, namely Tramadol and Hexymer, without authorization and without pharmaceutical competence, thereby fulfilling the elements of a criminal offense as regulated under Article 435 paragraph (2) of Law Number 17 of 2023 concerning Health. The court’s decision imposing a prison sentence of 1 year and 9 months is considered consistent with the provisions of health law because it takes into account the fulfillment of the criminal elements, trial facts, and the principle of proportionality in sentencing. This study recommends strengthening the supervision of hard drug distribution by the government and the Indonesian Food and Drug Authority, as well as ensuring consistent law enforcement against perpetrators of illegal pharmaceutical preparations circulation.